Answer:
y = 5x - 14
Step-by-step explanation:
First point coordinates
x₁
5
y₁
11
Second point coordinates
x₂
7
y₂
21
Result
Slope (m)
5
m = 10 / 2 = 5 / 1 = 5
Your function
The entered points belong to an increasing, linear function.
Equation: y = 5x - 14.
Hope i helped :)
Answer:
not sure for the 1st one but pretty sure 2nd one is B
Step-by-step explanation:
Find <span>tan<span>(<span><span>5π</span>12</span>)</span></span> and sin ((5pi)/12)
Answer: <span>±<span>(2±<span>√3</span>)</span>and±<span><span>√<span>2+<span>√3</span></span></span>2</span></span>
Explanation:
Call tan ((5pi/12) = t.
Use trig identity: <span><span>tan2</span>a=<span><span>2<span>tana</span></span><span>1−<span><span>tan2</span>a</span></span></span></span>
<span><span>tan<span>(<span><span>10π</span>12</span>)</span></span>=<span>tan<span>(<span><span>5π</span>6</span>)</span></span>=−<span>1<span>√3</span></span>=<span><span>2t</span><span>1−<span>t2</span></span></span></span>
<span><span>t2</span>−2<span>√3</span>t−1=0</span>
<span>D=<span>d2</span>=<span>b2</span>−4ac=12+4=16</span>--> <span>d=±4</span>
<span>t=<span>tan<span>(<span><span>5π</span>12</span>)</span></span>=<span><span>2<span>√3</span></span>2</span>±<span>42</span>=2±<span>√3</span></span>
Call <span><span>sin<span>(<span><span>5π</span>12</span>)</span></span>=<span>siny</span></span>
Use trig identity: <span><span>cos2</span>a=1−2<span><span>sin2</span>a</span></span>
<span><span>cos<span>(<span><span>10π</span>12</span>)</span></span>=<span>cos<span>(<span><span>5π</span>6</span>)</span></span>=<span><span>−<span>√3</span></span>2</span>=1−2<span><span>sin2</span>y</span></span>
<span><span><span>sin2</span>y</span>=<span><span>2+<span>√3</span></span>4</span></span>
<span><span>siny</span>=<span>sin<span>(<span><span>5π</span>12</span>)</span></span>=±<span><span><span>√<span>2+<span>√3</span></span></span>2</span></span></span>
You have to multiply whats outside the parenthesis with everything that is inside, so
![x^{-3}y^0.(x^2-3x^5y^4)](https://tex.z-dn.net/?f=x%5E%7B-3%7Dy%5E0.%28x%5E2-3x%5E5y%5E4%29)
![x^{-3}y^0.x^2-x^{-3}y^0.3x^5y^4](https://tex.z-dn.net/?f=x%5E%7B-3%7Dy%5E0.x%5E2-x%5E%7B-3%7Dy%5E0.3x%5E5y%5E4)
Multiplication of same bases we sum the exponents
![x^{-3+2}y^0-3x^{-3+5}y^{0+4}](https://tex.z-dn.net/?f=x%5E%7B-3%2B2%7Dy%5E0-3x%5E%7B-3%2B5%7Dy%5E%7B0%2B4%7D)
![x^{-1}.1-3x^2y^4](https://tex.z-dn.net/?f=x%5E%7B-1%7D.1-3x%5E2y%5E4)
![x^{-1}-3x^2y^4](https://tex.z-dn.net/?f=x%5E%7B-1%7D-3x%5E2y%5E4)
Alternative B.
x²-6x=0
x(x-6)=0
Two solutions are possible:
x=0
x=6